IMPLEMENTASI KEBIJAKAN KEAMANAN LINGKUNGAN BELAJAR PADA PAUD INKLUSIF - Yarliani, Ikta; Koenarso, Dyah Ageng Pramesty (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2025)
Inclusive early childhood education (ECED) ensures all children, including those with special needs, have access to a safe learning environment. This study examines the implementation of safety policies in inclusive ECED institutions in Banjarmasin and Banjarbaru using a phenomenological approach. Data were collected through in-depth interviews, document analysis, and observations, following stages of participant selection, interviews, transcription, coding, theme development, and interpretation. Findings indicate that while safety policies are implemented, challenges remain in infrastructure, teacher training, and community awareness. Limited resources, inadequate facilities, and low parental understanding hinder inclusivity. However, teacher training and policy adaptation have improved inclusive practices. To enhance implementation, stronger government support is needed in funding, regulations, and public awareness. Key recommendations include (1) allocating budgets for inclusive infrastructure, (2) mandating specialized teacher training, (3) integrating community engagement programs, and (4) establishing monitoring mechanisms. These measures can create a more inclusive and supportive learning environment.